Reconstruction of the Social Capital-Based Agricultural Extension System in the Tengger Tribe Society in Tosari, Pasuruan, East Java, Indonesia - Ugik Romadi; Kliwon Hidayat; Keppi Sukesi; Yayuk Yuliati (Agriekonomika, 2021)
This study aims to examine the “how” and “what kind of” implementation process of extension by the needs of the Tengger Tribe in optimizing their social capital as an effort to accelerate the process of information and technology transfer to achieve the goals of extension that have been outlined in the philosophy of extension, namely behavior change farmers as an effort to improve welfare. This research useed a qualitative approach with a phenomenological method. Based on the research found that a system and implementation of extension were needed by local conditions, and accommodates tribe characteristics. The reconstruction of the extension system must be carried out thoroughly in terms of the institutional aspects of extension, extension workforce, and implementation of extension so that it could achieve the expected goals of changing farmer’s behavior to improve the welfare of farmers in the Tosari Sub-District of Pasuruan Regency.